Health profiles in patients with chronic diseases in a highcomplexity health institution - Barrientos Gómez, Juan Guillermo; Pineda Jiménez, Laura María; Zapata Zuluaga, Natalia; Vélez Granda, Aura María; Echavarría Noreña, María Manuela; Montoya Botero, Isabella (Medicina UPB, 2020)
Objective: to describe the different profiles in terms of health-related quality of life found in patients with chronic diseases in a high-complexity health institution.Methodology: cross-sectional descriptive study that evaluated the health-related quality of life through the EQ-5D instrument, in patients with chronic diseases that consulted Internal Medicine and its subspecialties in the outpatient service of a highly-complexity health institution in the city of Medellin, during the year 2017.Results: 158 patients between the ages 46-68 (an average of 58-year-old) were surveyed. A total of 117 patients (74.1%) were female. The time of evolution from the age when the diagnostic was run to the actual age of the patient when surveyed was 8.7 years. The general health status of the patients from Endocrinology and Rheumatology was found to be of 80 points, being the feelings of “pain or discomfort” and “anxiety or depression” the ones that most affected the quality of life Additionally, in patients with infectious pathologies the general health status was the lowest (62.5); the most common factor was “pain or discomfort).Conclusions: it is evident that there is greater alteration in the variables of the EQ-5D of “pain or discomfort” and “anxiety or depression” in the general population, as well as in the females and the areas of Endocrinology and Rheumatology.
Keywords: health related quality of life; health profile; chronic disease; endocrinology; rheumatology